THE SPECIFICITY OF THE PROFESSIONAL ADAPTATION OF THE MANAGERIAL STAFF OF DIFFERENT GENERATIONS - M. V. Iontseva; A. A. Avdeeva (Вестник университета, 2020)
The problem of adaptation to professional activity among representatives of different generations is acute. Currently, managers understand the need and importance of the adaptation process for new employees. But they do not always take into account the fact that employees belonging to different generations may not only have radically different views on the same problems, but also the process of adaptation may take place in different ways, using different socio-psychological mechanisms of adaptation. Using the example of generation X and generation Y the psychological features that make it possible to pass the adaptation period most effectively have been considered in the article. The most distinctive characteristics of representatives of different generations have been highlighted.